Dendronised diazapyrenium derivatives: host–guest complexes in aqueous solution. (12th September 2018) - Molloy, Jennifer K.; Bergamini, Giacomo; Baroncini, Massimo; Hahn, Uwe; Ceroni, Paola
Abstract : Water soluble dendrimers, containing a diazapyrenium core, bind CB[7] with a higher association constant than CB[8]. Abstract : Dendronised diazapyrenium derivatives were synthesised with glycol-appended dendrons to confer water solubility. These dendrimers form self-assembled supramolecular structures with cucurbituril hosts. The self-assembly process could be monitored by changes in the absorption spectra and redox properties of the dendrimers due to electronic interactions of the electron-accepting diazapyrenium core with the electron-rich inner cavity of cucurbiturils.